2014
DOI: 10.1007/s00203-014-1052-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and biogeography of the invasive cyanobacterium Cylindrospermopsis raciborskii

Abstract: Cylindrospermopsis raciborskii is a toxic cyanobacterium with an invasive nature. The species is found in all the main continents but its origin and dispersal routes on a worldwide perspective remain yet mostly unknown. In this study, 27 isolates of C. raciborskii gathered worldwide have been used for an in-deep phylogenetic analyses with a concatenated system of three genetic markers (16 rRNA, 16S-23S ITS larger subunit, and RNA polymerase rpoC1) comprehending 3,188 bp. Our results provide support for an orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…4), in agreement with other studies (Stüken et al, 2006;Moreira et al, 2015;Dokulil, 2015). Vegetative cells of C. raciborskii can survive at low temperatures (<12°C) and low light intensities, as found in Alte Donau Lake (Dokulil, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…4), in agreement with other studies (Stüken et al, 2006;Moreira et al, 2015;Dokulil, 2015). Vegetative cells of C. raciborskii can survive at low temperatures (<12°C) and low light intensities, as found in Alte Donau Lake (Dokulil, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…raciborskii has been shown to produce hepatotoxic cylindrospermopsin and neurotoxic saxitoxins (Wood and Stirling, 2003;Molica et al, 2005). This species originates from tropical regions and currently expands its distribution in temperate regions, therefore it may be considered an invasive species in European waterbodies (Padisák, 1997;Moreira et al, 2015). In this study C. raciborskii was isolated from shallow hypereutrophic Manyas Lake but did not contain the mcyE gene.…”
Section: Discussionmentioning
confidence: 84%
“…One such species is Cylindrospermopsis raciborskii, a nitrogen-fixing toxic cyanobacterium spreading in temperate regions across the world that is capable of altering local ecosystem processes when dominant (Padisák, 1997;Isvánovics et al, 2000). Recent phylogenetic evidence has suggested that the species originated in the American tropics (Moreira et al, 2015) and its distribution was once thought to be restricted to the tropics and subtropics, where it co-occurs with other bloom-formers such as Microcystis aeruginosa and Anabaena sp. (Marinho & Huszar, 2002;Molica et al, 2005;Soares et al, 2009;Moisander et al, 2012).…”
Section: Introductionmentioning
confidence: 98%